Masquerades of Cluster Headache - Khoo, SB (Malays Fam Physician, 2009)
Many cluster headache (CH) patients waited several years to be accurately diagnosed because their symptoms are often mistaken for sinusitis or a dental disorder.1 Patients have also been mistakenly diagnosed as analgesic drug abusers or suffering from a psychiatric illness. This case report illustrates how a young lady was diagnosed to have cluster headache after several years of consultations with ophthalmologists for eye swelling and redness. It also highlights the importance of pain assessment and a general and holistic approach to medical care which is the main distinguishing feature of Family Medicine.